Storytelling in management practice : dynamics and implications - Reissner, Stefanie; Pagan, Victoria (Management, organizations and society (London, England) ;, 2013)
Since the early 2000s, storytelling as a means of managerial communication has been increasingly advocated, with a focus on the management practices of leadership, change and organizational culture. Most research on storytelling in management practice derives from practitioner experience, but little is known about the specific dynamics behind storytelling as a tool for managerial communication. This book derives from one of the first research studies into storytelling in management practice, which sought to evaluate the assumed, but not necessarily proven, effectiveness of storytelli.